Reclassification of diabetes aetiology in a family with multiple diabetes phenotypes - Kavvoura, F; Raimondo, A; Thanabalasingham, G; Barrett, A; Webster, A; Mann, N; Ellard, S; Gloyn, A; Owen, K (Endocrine Society, 2013)
Background: Maturity-onset diabetes of the young (MODY) is uncommon; however, accurate diagnosis facilitates personalized management and informs prognosis in probands and relatives. Objective: The objective of the study was to highlight that the appropriate use of genetic and nongenetic investigations leads to the correct classification of diabetes etiology. Case Discussion: A 30-year-old European female was diagnosed with insulin-treated gestational diabetes. She discontinued insulin after delivery; however, her fasting hyperglycemia persisted. β-Cell antibodies were negative and C-peptide was 0.79 nmol/L. Glucokinase (GCK)-MODY was suspected and confirmed by the identification of a GCK mutation (p.T206M). Methods: Systematic clinical and biochemical characterization and GCK mutational analysis were implemented to determine the diabetes etiology in five relatives. Functional characterization of GCK mutations was performed. Results: Identification of the p.T206M mutation in the proband's sister confirmed a diagnosis of GCKMODY. Her daughter was diagnosed at 16 weeks with permanent neonatal diabetes (PNDM). Mutation analysis identifiedtwoGCKmutations thatwereinherited in trans-p. [(R43P);(T206M)], confirming a diagnosis of GCK-PNDM. Both mutations were shown to be kinetically inactivating. The proband's mother, other sister, and daughter all had a clinical diagnosis of type 1 diabetes, confirmed by undetectable C-peptide levels and β-Cell antibody positivity. GCK mutations were not detected. Conclusions: Two previously misclassified family members were shown to have GCK-MODY, whereas another was shown to have GCK-PNDM. A diagnosis of type 1 diabetes was confirmed in three relatives. This family exemplifies the importance of careful phenotyping and systematic evaluation of relatives after discovering monogenic diabetes in an individual. © 2014 by the Endocrine Society.